2015
DOI: 10.1007/s00264-015-2792-9
|View full text |Cite|
|
Sign up to set email alerts
|

Revision surgery after third generation autologous chondrocyte implantation in the knee

Abstract: Revision surgery after third generation autologous chondrocyte implantation is common and is needed primarily in cases with arthrofibrosis, partial graft cartilage deficiency and symptomatic bone marrow oedema resulting in a significantly better clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
1
23
1
1
Order By: Relevance
“…Niethammer et al 18 investigated the common revision operations after third-generation ACI (NOVOCART 3D; TETEC AG, Reutlingen, Germany) in a population of 143 consecutive patients (171 cartilage defects; mean defect size, 5 cm 2 ) with a mean follow-up of 5 years. The revision rate was 22.4% ( n = 32) with a mean time to revision of 1.15 years (15 MF/drilling, 7 arthrolysis, 3 ACI, 3 arthroscopy, 2 retrograde drilling, 1 arthroplasty, and 1 HTO).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Niethammer et al 18 investigated the common revision operations after third-generation ACI (NOVOCART 3D; TETEC AG, Reutlingen, Germany) in a population of 143 consecutive patients (171 cartilage defects; mean defect size, 5 cm 2 ) with a mean follow-up of 5 years. The revision rate was 22.4% ( n = 32) with a mean time to revision of 1.15 years (15 MF/drilling, 7 arthrolysis, 3 ACI, 3 arthroscopy, 2 retrograde drilling, 1 arthroplasty, and 1 HTO).…”
Section: Resultsmentioning
confidence: 99%
“…In the study population evaluated by Niethammer et al, 18 of the 143 patients with 171 defects treated with third generation ACI (NOVACART 3D, TETEC AG, Reutlingen, Germany), 34 (19.9%) of these defects had previous failed cartilage repair procedures. At statistical analysis, cartilage defects with second-line therapy after a previously performed cartilage repair before ACI, showed no higher complication or revision rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings make AFS cells very attractive for cell‐based articular cartilage repair. However, practical experience with ACI has shown that the differentiation efficiency of the donor cells determines successful clinical outcome [11]. Therefore, AFS‐cell‐based transplantation approaches will rely on efficient ways to differentiate cells before or during the transplantation process.…”
Section: Introductionmentioning
confidence: 99%
“…However, delamination or disturbed fusion to the surrounding native cartilage and subchondral bone are still problems for the third-generation ACI. Niethammer et al 74 reported a revision rate of 23.4% after MACT. The reasons were bone marrow edema, arthrofibrosis, and partial graft deficiency.…”
Section: Developments In Acimentioning
confidence: 99%